RESIDENTIAL INTERIOR DESIGN CHARACTERISTICS OF THE ANALYSIS IN THE PERIOD (European Journal of Interdisciplinary Research and Development, 2022)
In this article, the main task is to identify the most effective design methods and the sequence of development of a design concept.